In vitro Modulation of the LPS-Induced Proinflammatory Profile of Hepatocytes and Macrophages- Approaches for Intervention in Obesity? - Kheder, Ramiar K.; Hobkirk, James; Stover, Cordula M. (Frontiers in Cell and Developmental Biology, 2016)
Low grade endotoxemia is a feature of obesity which is linked to development of steatohepatitis in non-alcoholic fatty liver disease. In this study, macrophages (J774) and hepatocytes (HepG2) were stimulated with lipopolysaccharide (LPS) from E.coli 0111: B4 and analysed for modulation of this response when preconditioned or stimulated subsequent to LPS, with different doses of Vitamin D3 or docosahexaenoic acid (DHA) over a time period of one and five days. Pro-inflammatory TNF and pro-fibrotic TGF released into the supernatants were measured by ELISA. qPCR was performed for Srebp-1c and PPAR mRNA (genes for products involved in fatty acid synthesis and catabolism, respectively). Vitamin D3 and DHA exerted a consistent, dose dependent anti-inflammatory effect and increased PPAR relative to Srebp-1c in both cell types. By contrast, addition of free fatty acids (FFA, oleic acid/palmitic acid 2:1) caused aggravation of LPS-induced inflammatory reaction and an increase of Srebp-1c relative to PPAR. Our results argue in favour of dietary supplementation of Vitamin D3 or DHA (and avoidance of monounsaturated/saturated fatty acids) to alleviate development of fatty liver disease.